Cryopreservation of hairy root culture of Amrithapala, Decalepis arayalpathra (Joseph & Chandras) Venter - Dhanya C S (Department of Plant Biotechnology, College of Agriculture, 2014)
The present study, “Cryopreservation of hairy root culture of Decalepis arayalpathra (Joseph & Chandras.) Venter” was carried out at the Biotechnology and Bioinformatics Division, Jawaharlal Nehru Tropical Botanic Garden and Research Institute, Palode during 2013-2014. The objective of the study is to find an efficient cryopreservation protocol for hairy root culture of Decalepis arayalpathra and a comparative analysis of secondary metabolite profile. Hairy roots of Decalepis arayalpathra, a critically endangered medicinal plant used by Kani tribes as an effective remedy for peptic ulcer and cancer like afflictions were attempted to cryopreserve using encapsulation-dehydration and vitrification methods. A comparative analysis of secondary metabolite profile of cryopreserved and normal hairy roots was also made to examine practical utility of cryopreserved hairy roots. Encapsulation-dehydration method was not good for preserving hairy roots of D. arayalpathra in liquid nitrogen. The roots were highly sensitive to sucrose in pre-culture solution at least to get dehydration tolerance. Encapsulated root tips pre-cultured with 0.5 M sucrose did not survive even after one hour dehydration. Inclusion of DMSO in the pre-culture solutions improved dehydration tolerance of encapsulated root tips but did not support LN tolerance. Hairy root tips (2-3 mm) pre-cultured on half strength Murashige and Skoog (MS) solid medium with 0.1 mg/l 2, 4-D for two days followed by exposure to PVS2 for 45 min gave 50-100 percent recovery and regeneration after cryopreservation. Roots regenerated from cryopreserved root tips grew like normal hairy roots showing similar secondary metabolite profile as revealed by thin layer chromatography. HPLC profiling of MBALD compound in cryopreserved root during first subculture passage was less compared to that of the normal hairy root culture. The study revealed cryopreservation by vitrification as a useful method to preserve hairy root of D. arayalpathra.